Human-animal interaction in the context of supporting development. A review of selected animal species used in children's therapy - Katarzyna Nosek-Kozłowska (Rozprawy Społeczne)
The aim of the article is to analyze the role and significance of the presence of animals in supporting children’s development in the context of selected psychological, social, and educational aspects. To gather empirical material, the method of literature analysis was used, aiming to identify the main mechanisms and benefits of interactions between children and animals, as well as to present key conclusions based on available scientific sources. Based on the materials used it explores the numerous benefits of animal-assisted therapy, such as fostering empathy, cultivating a sense of responsibility, and enhancing interpersonal skills. Moreover, interaction with animals contributes to stress reduction, improved mental well-being, and the facilitation of socialization processes. Engagement with four-legged companions is shown to play a pivotal role in children’s emotional, social, and cognitive growth. The article emphasizes the therapeutic value of animal interaction, particularly in supporting children with developmental challenges. It reflects on how caring for and engaging with animals can serve as a vital component of a developmental support system, promoting social integration, fostering positive attitudes, and enhancing social competencies.